2008
DOI: 10.1093/eurheartj/ehn417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aspirin dose on ischaemic events and bleeding after percutaneous coronary intervention: insights from the PCI-CURE study

Abstract: In this large observational analysis of patients undergoing PCI, low-dose aspirin appeared to be as effective as higher doses in preventing ischaemic events but was also associated with a lower rate of major bleeding and an improved net efficacy to safety balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 28 publications
1
52
0
3
Order By: Relevance
“…However, rates of major bleeding were not lower with radial versus femoral access in patients with STEMI, though rates of major vascular complications were significantly reduced. 561 Although arterial closure devices have been associated with decreased femoral access site bleeding, more rapid hemostasis, and shorter duration of bed rest, 251,562,563 their routine use cannot be advocated specifically to reduce vascular complications after PCI, given the lack of robust, directionally consistent data on their efficacy and safety compared with manual compression. [564][565][566] Retroperitoneal bleeding should be suspected when the following are seen: unheralded intraprocedural or postprocedural hypotension and bradycardia (or tachycardia), high vascular puncture site, and an otherwise unexplained decrease in hemoglobin.…”
Section: Vascular Access Site Bleedingmentioning
confidence: 99%
“…However, rates of major bleeding were not lower with radial versus femoral access in patients with STEMI, though rates of major vascular complications were significantly reduced. 561 Although arterial closure devices have been associated with decreased femoral access site bleeding, more rapid hemostasis, and shorter duration of bed rest, 251,562,563 their routine use cannot be advocated specifically to reduce vascular complications after PCI, given the lack of robust, directionally consistent data on their efficacy and safety compared with manual compression. [564][565][566] Retroperitoneal bleeding should be suspected when the following are seen: unheralded intraprocedural or postprocedural hypotension and bradycardia (or tachycardia), high vascular puncture site, and an otherwise unexplained decrease in hemoglobin.…”
Section: Vascular Access Site Bleedingmentioning
confidence: 99%
“…80 In a post hoc analysis of data from PCI-CURE, patients were stratifi ed into three groups based on aspirin dose ( Ն 200, 101-199, and Յ 100 mg). 81 All three groups had similar rates of the composite end point of cardiovascular death, MI, or stroke at long-term follow-up (8.6%, 7.4%, 7.1%, respectively). Major bleeding was signifi cantly increased with high-dose aspirin compared with medium-or low-dose aspirin (3.9%, 1.5%, 1.9%, respectively).…”
Section: Aspirin Dose Following Pci With Stent Placementmentioning
confidence: 80%
“…5,8,[10][11][12] Although these data generally favor low-dose aspirin, there are few comparative data evaluating aspirin dose and long-term outcomes among contemporary MI patients, especially those who are concurrently treated with more potent ADP receptor inhibitors such as prasugrel and ticagrelor. Exploratory analyses from the Platelet Inhibition and Patient Outcomes (PLATO) study suggested that higher doses of aspirin might have neutralized the benefit of more potent ticagrelor over clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies and post hoc analyses of clinical trial data suggested no benefit and potentially increased harm with high-dose aspirin use. [5][6][7][8][9][10][11] More recently, a factorial randomized trial of double-versus standard-dose clopidogrel and high-versus low-dose aspirin found similar outcomes in high-versus low-dose aspirin users, but patients were followed for only 1 month. 12 Based on these limited data, the American Heart Association/American College of Cardiology guidelines recently revised the recommendations to change the maintenance dose from high dose to low dose.…”
mentioning
confidence: 99%